Desire and the Law of the Father in Oral Narratives in the Context of Lacan's Mirror Phase: The Process of Subjectivization in the Karayılan Tale - Yorganci, Osman Kursat (GELENEKSEL YAYINCILIK LTD STL, 2024)
Tale, one of the narrative genres of folk literature, presents a world characterized by its own symbolic motifs through the mysterious and magical structure of its time and space elements and the typological features of its characters. However, when these unique worlds of tales are mirrored to see beyond their surface meanings, it is understood that the deep meanings of the narratives at the textual level are not far from the reality of the real world. Inaddition to this reality, tales can also be considered as cultural topographies in which the sociogenetic codes of the society are loaded. If we analogize culture to an ancient route that connects the past with the present and the present with the future, tales can be considered as milestones or bridges that are both the creators and carriers of the roads on this route. Humans have pursued their efforts to comprehend, make sense of and interpret by generating literary products throughout the historical eras. Even though the reality of literature and the reality of life are not the same; emotions, thoughts, experiences and dreams have been conveyed through literary works and thus human, environment and society have been formed. In this respect, fairy tales are actually literary products in which the reality of life is reflected in literature. From the time when writing has not yet been widely used to the present day, tales have enabled the processing and development of the language it has kept alive and the transfer of cultural codes to social life; conflicts such as good-evil, right-wrong, hardworking-lazy, honest-liar, and the conflict elements of narratives such as distress, anxiety, despair, illness and death, which are shaped around desire, the object of desire and the law of the father, have shaped the world of mind, sometimes with the ordinary flow of life and sometimes with a surreal and unconscious dimension that exceeds the boundaries of reason and real life. Inthis regard, tales are an expression and a manifestation of the individual and collective subconscious, from the imaginary to the symbolic and eventually to the real. In this study, based on the idea of contributing to both the research of extinct oral culture values, which are considered as one of the two main ways in which folklore has continued its development since the early periods of enlightenment when folklore has started to find its place in social and human sciences, and to the preservation and survival of folklore and its transmission from generation to generation by approaching intangible cultural heritage products with new methods and new productions; this study intends to reveal the influence of Lacan's Mirror Stage, which has a determinant role in the cognitive and affective development of individuals, on the tale of Karay & imath;lan, which is a legendary oral narrative type, in the context of psychoanalytic structure. For this purpose, in the introduction part of the study, firstly, the use of psychoanalysis as a literary criticism method in the analysis of literary products is discussed; then under the first heading, the Mirror Stage The Imaginary, The Symbolic, The Real tripartite model of Lacanian Psychoanalysis, which forms the basis of the study, and the concepts of Desire and The Law of the Father, which are the concepts of this model accepted as the basis for analysis, are discussed; and then, under the second heading, the tale of Karay & imath;lan was analyzed by taking the concepts of Desire and Law of the Father into consideration. Inthe tale, Karay & imath;lan's subjectivization process began with birth and milk, which corresponds to the concept of mirror in the Mirror Stage, and proceeded with learning to read through his mother's discourse and language. Finally, it was understood that it was completed with marriage in the symbolic period by being subject to law of the father and obeying the symbolic order, once again with the help of language. As in oral narratives in general, the Lacanian psychoanalytic analysis applied to the tale of Karay & imath;lan reveals that the basic structure of the narrative is formed by archetypal reflections, that the world of beings and objects is actually a view of the subconscious, whose symbolism is reflected, and for this reason, tales and other oral narrative genres are in need of re-analysis from this different and new perspective. In addition, it has been found that the formulation of psychoanalytic literary text analysis as a method and its use particularly in the analysis of genres with intense archetypal elements like tales will contribute to the formation of different perspectives in the field.
Keywords: Karay & imath; lan tale; Lacanian psychoanalysis; mirror stage; desire; law of the father; Arts & Humanities - Other Topics